The role of growth and maturation in the physical development of youth male soccer players - Gundersen, H.; Grendstad, H.; Rygh, C. B.; Hafstad, A.; Vestbøstad, M.; Algerøy, E.; Smith, O. R. F.; Joensen, M.; Kristoffersen, M. (International Journal of Sports Medicine, 2025)
Biological maturation and growth influence youth athletes` physical performance during adolescence. However, how this association develops over time remains unclear. Thus, this study examined associations between biological maturity and sprint speed, vertical jumping ability, leg strength, and aerobic capacity between ages 14.1 and 17.4 in youth male soccer players. A total of 103 players were followed. Performance in 40-m sprint, countermovement jump (CMJ), leg press, and maximal oxygen consumption (VO2max) was tested biannually at seven time points. Maturity was estimated using bone age from hand-wrist X-rays. Latent growth modelling examined changes in maturity-performance associations over time. Maturity was significantly (p < 0.05) associated with sprint, CMJ, leg strength (force and power), and VO2 max at ages 14.1, 14.7, and 15.3 years. The associations were, however, less significant over time. Specifically, maturity was no longer statistically associated with sprint and CMJ performance at 15.7 years, force and VO2 max at 16.4 years, and power at 16.8 years. There were no significant associations at 17.4 years. Biological maturity influences physical capacities during early adolescence, but its impact diminishes as players age. The timing of this decline appears to vary between physical performance domains, with sprint and jump performance stabilizing earlier than muscular strength and aerobic capacity.